2014
DOI: 10.4236/jmmce.2014.23019
|View full text |Cite
|
Sign up to set email alerts
|

Potentiality of Clay Raw Materials from Northern Morocco in Ceramic Industry: Tetouan and Meknes Areas

Abstract: International audienceThis study aims at evaluating the potential suitability of Tetouan and Meknes (central Morocco) clay material as raw materials in various ceramic applications by investigating their textural, chemical, thermal and firing characteristics. Textural properties were identified by specific surface area, cation exchange capacity (CEC) and bulk density (ρs). Chemical and thermal properties were assessed using XRF and TG/DTA techniques, respectively. Firing characteristics at temperatures from 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 29 publications
(33 reference statements)
1
23
0
1
Order By: Relevance
“…The micropore volume and total pore volume are in line with the work of ElOuahabi et al [25] in which the pore volume and total pore volume of some selected clay materials were recorded as 0.05 cm 3 /g and 0.015 cm 3 /g respectively. Surface area of 234m 2 /g as compared with the works of ElOuahabi et al [25] shows that BSG is a good candidate for Fe (III) ion removal. From the results of Table 2, it was observed that the mass of Iron (III) oxide (Fe2O3) present in BSG is low (1.243g/kg).…”
Section: Adsorption Kinetic Studiessupporting
confidence: 89%
“…The micropore volume and total pore volume are in line with the work of ElOuahabi et al [25] in which the pore volume and total pore volume of some selected clay materials were recorded as 0.05 cm 3 /g and 0.015 cm 3 /g respectively. Surface area of 234m 2 /g as compared with the works of ElOuahabi et al [25] shows that BSG is a good candidate for Fe (III) ion removal. From the results of Table 2, it was observed that the mass of Iron (III) oxide (Fe2O3) present in BSG is low (1.243g/kg).…”
Section: Adsorption Kinetic Studiessupporting
confidence: 89%
“…Due to the growing concern about the economy and the recovery of the basic ceramic industry in Morocco, it is becoming imperative and crucial to look for new raw materials containing magnesium. However, the main focus of discussion only to use three essential minerals forming the rocks: Magnesite, dolomite and lizardite situated in the Rif of Morocco, and which has other secondary materials: perlite, halloysite, diatomite, bentonite and red clays [24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The literature reports that small amount of coloring oxides such as Fe 2 O 3 and TiO 2 less than 0.9 % may be accepted for porcelain wares production. Hematite promotes glassy phase formation and at the same time may affect glassy phase formation due to its reduction to FeO 4 at higher sintering temperature [12,13]. When the porcelain samples were fired up to 1300 o C, high vitrification and densification of the porcelains was observed at 1250 o C, however at the sintering temperature greater than 1250 o C porcelains became more porous and did not maintain their regular shapes and started to melt as shown in Figure 2.…”
Section: Tab I Porcelain Bodies Formulations In Percentages Weight (mentioning
confidence: 99%